2015
DOI: 10.1038/jes.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

Gene-specific promoter methylation is associated with micronuclei frequency in urothelial cells from individuals exposed to organic solvents and paints

Abstract: Sufficient epidemiologic evidence has established an etiologic link between bladder cancer risk and occupational exposure as a painter to organic solvents. Currently, it remains to be established whether gene-specific promoter methylation contributes to bladder cancer development, including by enhancing chromosome breakage or loss. We investigated the effect of chronic exposure to organic solvents and paints on DNA methylation profiles in the promoter regions of four genes (GSTP1, p16(INK4a), APC and CDH1) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
7
0
2
Order By: Relevance
“…In this context, the detection of increased levels of MN in urothelial cells can be a useful approach to detect individuals prone to have bladder cancer, and/or to assess the prognosis of the pathology. Increased MN frequencies in urothelial cells of humans populations have been associated to those risk factors involved in bladder cancer such as tobacco (Zamani et al, ), arsenic (Paul et al, ), and occupational exposure to organic solvents (Hoyos‐Giraldo et al, ). Additionally, MN formation was detected in the bladder cells of rats exposed to orto‐phenylphenol, a fungicide and antibacterial agent well known as a bladder tumor inducer in rats (Balakrishnan and Eastmod, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the detection of increased levels of MN in urothelial cells can be a useful approach to detect individuals prone to have bladder cancer, and/or to assess the prognosis of the pathology. Increased MN frequencies in urothelial cells of humans populations have been associated to those risk factors involved in bladder cancer such as tobacco (Zamani et al, ), arsenic (Paul et al, ), and occupational exposure to organic solvents (Hoyos‐Giraldo et al, ). Additionally, MN formation was detected in the bladder cells of rats exposed to orto‐phenylphenol, a fungicide and antibacterial agent well known as a bladder tumor inducer in rats (Balakrishnan and Eastmod, ).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 150 non-smoking car painters from several workshops in the southwest of Colombia found a significant increase in DNA methylation in the promoter region of GSTP1 and p16 INK4a in exfoliated urothelial cells of exposed workers compared to references, and these gene-specific alterations were associated with an increase in micronuclei frequency [202], an indicator of genotoxicity. Because the exact chemical composition of the exposure is not reported here, the molecular findings can only be associated to the general category “occupational exposure as a painter,” which is one of the occupational exposures included in the IARC monograph volume 100F.…”
Section: Epigenetic Effects Associated With Carcinogenic Chemicalsmentioning
confidence: 99%
“…Particularly, Moro et al (24) observed an increase in oxidative damage in car painters. Recently, Hoyos-Giraldo et al (16) observed an association between years of occupational exposure as a painter and organic solvents levels in urothelial cells. As a matter of fact, some studies have already shown a positive association between car painting and DNA damage (25,26), but as far as we know, our study is the first to evaluate the occupational exposure of car painters using a multimarker test as BMCyt, unravelling not only the DNA damage status, but also potential cellular phenotypes associated with genome instability and alterations in the cellular kinetics as early biomarkers for future disease and cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is disturbing to know that literature is full of reports associating painting with cancer, especially considering that >90% of all human cancers are of epithelial origin (16,17,28). Recently, Jung et al (28) observed that Canadian painters occupationally exposed had high risk of lung cancer, corroborating the IARC classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation